Mechanical Properties and Corrosion Resistance of Magnesium–Hydroxyapatite Composites Fabricated by Spark Plasma Sintering - Ikuho Nakahata; Yusuke Tsutsumi; Equo Kobayashi (Metals, 2020)
Recent studies indicate that biodegradable magnesium alloys and composites are attracting a great deal of attention in orthopedic applications. In this study, magnesium–hydroxyapatite (Mg–HAP) composites with different compositions and grain size were fabricated by a spark plasma sintering (SPS) method. Their mechanical properties and corrosion behavior in a pseudo-physiological environment were investigated by pH measurements and inductivity coupled plasma (ICP) elemental analysis after an immersion test using Hanks’ solution. The results clearly showed that the addition of HAP improved both the mechanical properties and corrosion resistance. The results also indicated that the finer grain size improved most of the properties that are needed in a material for an orthopedic implant. Furthermore, the authors reveal that there is a strong correlation between the compressive strength and the porosity. In order to achieve the same compressive strength as human bone using these fabrication conditions, it is revealed that the porosity should be lower than 1.9%.